2012
DOI: 10.1002/term.1462
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light-irradiated photocrosslinkable chitosan hydrogel to prevent bone formation in both rat skull and fibula bone defects

Abstract: In the field of orthopaedic surgery, an orthopaedic surgeon sometimes requires to suppress excessive bone formation, such as ectopic bone formation, ossifying myositis and radio-ulnar synostosis, etc. Ultraviolet (UV) light irradiation of a photocrosslinkable chitosan (Az-CH-LA) generates an insoluble hydrogel within 30 s. The purpose of this study was to evaluate the ability of the photocrosslinked chitosan hydrogel (PCH) to inhibit bone formation in an experimental model of bone defect. Rat calvarium and fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The histological sections post 8-week implantation are processed by methylene-fuchsin staining, and the results are shown in Figure d,e. At a defect site, once the bone defect is occupied by fibrous tissue, it is hard to have further bone formation. The fibrous tissue, in addition, contributes to the weak bone-bonding between the samples and tissue. A thick covering of fibrous tissue encompassing the PEEK samples can be observed and the tissue is easy to peel off from the PEEK surface, which indicates a weak osseointegration of flat surface.…”
Section: Resultsmentioning
confidence: 99%
“…The histological sections post 8-week implantation are processed by methylene-fuchsin staining, and the results are shown in Figure d,e. At a defect site, once the bone defect is occupied by fibrous tissue, it is hard to have further bone formation. The fibrous tissue, in addition, contributes to the weak bone-bonding between the samples and tissue. A thick covering of fibrous tissue encompassing the PEEK samples can be observed and the tissue is easy to peel off from the PEEK surface, which indicates a weak osseointegration of flat surface.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan hydrogel has also been investigated to prevent excessive bone formation. Using a photocrosslinkable chitosan hydrogel (Az-CS-LA), Tsuda et al demonstrated the ability of the hydrogel to effectively prevent ectopic bone formation for up to 8 weeks in a rat model with calvarium and fibula defects [79]. In native ECM, the presence of sulfated polysaccharides such as chondroitin sulfate plays an essential role to bind and retain growth factors to support cell functions.…”
Section: Orthopedic Regenerative Engineeringmentioning
confidence: 98%
“…The lactose group made the Az-CS-LA polymer water soluble. Briefly, the hydrogels were prepared by exposing a solution of Az-CH-LA 20 mg/mL to UV light for 30 s [79]. Gelation time was dependent on the intensity of UV radiation; the higher the intensity, the lower the gelation time.…”
Section: Photocrosslinked Hydrogelsmentioning
confidence: 99%
“…To date, various photocrosslinked hydrogels have been investigated as materials that can be used as drug‐delivery systems and tissue engineering. These hydrogels were prepared via a photochemical reaction using mono‐, di‐, or multifunctional vinylated monomers or macromers, including HEMA, poly(ethylene glycol) dimethacrylate, poly(ethylene glycol) diacrylate, methacrylated sebacic acid, azide and lactose moieties introduced in chitosan, and styrenated gelatin …”
Section: Introductionmentioning
confidence: 99%